Disadvantaged Family's Quality of Life and Psychosocial Environment on Growth and Development of Infants - Zulfa Febriani; Melok Roro Kinanthi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2022)
Stunting, a condition characterized by poor growth and development, has become a significant public health concern in Indonesia. Therefore, the current study adopts a correlational design and aims to explore the relationship between family quality of life, psychosocial environment, and the growth and development of under-two-year-old infants from low socioeconomic status. To conduct the study, 720 mothers were selected through cluster sampling in Pandeglang Regency. Family quality of life and psychosocial environment were measured using the BC-FQoL and HOME-SF tools, respectively. Nutritional status was determined based on height-for-age (H/A) and weight-for-age (W/A) to evaluate growth and development. The results showed that there was no significant relationship between family quality of life, psychosocial environment, and nutritional status. Weight-for-age had a weak but significant relationship with emotional well-being, family interaction, and emotional psychosocial stimulation. Height-for-age was only related to emotional well-being, indicating the need to consider the psychosocial situation and family involvement in caring for infants.